2002
DOI: 10.1038/sj.jhh.1001314
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study on association of calcium intake with blood pressure in Japanese population

Abstract: To investigate the association of calcium intake independently of other nutrients already known as predictors of hypertension, a cross-sectional study was carried out on the same population in Japan as used for the INTERSALT study. Dietary calcium intake was estimated from a 1-day 24-h recall. Sodium and potassium intakes were evaluated by 24-h urinary excretion. Data from 476 subjects aged 20-59 years, 230 men and 246 women, were analysed. The mean dietary calcium intake ranged from 557 to 608 mg/day among me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
6
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 24 publications
3
6
0
1
Order By: Relevance
“…The associations were more obvious and stronger for systolic than diastolic blood pressure. These results are in agreement with most observational studies and randomized trials [1][2][3][4][5][6][7][26][27][28][29]. Moreover, our results show that the association with blood pressure was stronger when the consumption of both dairy products and dietary calcium was high, suggesting a specific effect of calcium and other biological components of dairy products on blood pressure.…”
Section: Discussionsupporting
confidence: 92%
“…The associations were more obvious and stronger for systolic than diastolic blood pressure. These results are in agreement with most observational studies and randomized trials [1][2][3][4][5][6][7][26][27][28][29]. Moreover, our results show that the association with blood pressure was stronger when the consumption of both dairy products and dietary calcium was high, suggesting a specific effect of calcium and other biological components of dairy products on blood pressure.…”
Section: Discussionsupporting
confidence: 92%
“…Lower consumption of calcium has also been reported earlier in adolescents [7]. Beneficial effects of increased calcium intakes/supplementation with calcium on BP have also been reported [8,9]. Mushengezi, et al [10] reported higher BMI and WC as predictor of mean arterial pressure (MAP), whereas our results indicate that body fat% and WC were predictors of BP.…”
supporting
confidence: 82%
“…14,15 Previous studies also showed significant correlations between Ca intake and urinary potassium (UK) excretions. 16 Because of these reasons, one would expect a positive association between milk consumption frequencies and UCa and UK excretions. Therefore, the present study evaluated milk consumption frequencies measured by proxy FFQ administrations among children enrolled in the IDEFICS study, by comparing with UCa and UK concentrations derived from spot urine samples.…”
mentioning
confidence: 99%